ECONOMIC MECHANISM OF LOGISTIC CLUSTER FUNCTIONING - Vladimir I. Stepanov; Ol'ga V. Rykalina (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article provides a functional-processional scheme for the economic mechanism of regional logistic cluster functioning based on principles of its building and potential opportunities of Russian Federation regions. The authors propose a classification of principles for forming the economic mechanism of regional logistic cluster functioning, which includes economic, organizational, structural, social and technological groups. They discuss qualitative and quantitative components of the economic mechanism, including security in managing delivery chains and existing risks in logistic activity. All components of the scheme for the economic mechanism of the logistic cluster are accompanied by material, information and finance flows.